2011
DOI: 10.1038/msb.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Deep proteome and transcriptome mapping of a human cancer cell line

Abstract: More than 10 000 proteins were identified by high-resolution mass spectrometry in a human cancer cell line. The data cover most of the functional proteome as judged by RNA-seq data and it reveals the expression range of different protein classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

67
862
6
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(950 citation statements)
references
References 35 publications
67
862
6
15
Order By: Relevance
“…These values are in good agreement with estimates reported in previous large‐scale proteomics studies (Nagaraj et al , 2011; Kulak et al , 2014; Hein et al , 2015), and this adds confidence to our use of γ‐tubulin data for calibration purposes. Also, we emphasize that although this calibration is critical for calculations of exact absolute copy numbers, any future correction of γ‐tubulin abundance would not affect relative numbers or any of the major conclusions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These values are in good agreement with estimates reported in previous large‐scale proteomics studies (Nagaraj et al , 2011; Kulak et al , 2014; Hein et al , 2015), and this adds confidence to our use of γ‐tubulin data for calibration purposes. Also, we emphasize that although this calibration is critical for calculations of exact absolute copy numbers, any future correction of γ‐tubulin abundance would not affect relative numbers or any of the major conclusions.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the centrosomal proteins studied here are expected to be expressed at low levels, and information about their abundance remains scarce. In comprehensive proteomics studies, key regulators of centriole duplication, including Plk4, Sas‐6, and STIL, were barely detectable, if they were detected at all (Beck et al , 2011; Nagaraj et al , 2011). For example, one extensive mass spectrometry‐based analysis of U2OS cells concluded that Sas‐6 is expressed at fewer than 500 copies per cell (Beck et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in methods and instruments for mass spectrometry enable quantitative proteomics analysis of complex samples with good coverage (1)(2)(3)(4). Several techniques for quantification by mass spectrometry exist, both using isotopic labeling and label free methods (5,6).…”
mentioning
confidence: 99%
“…Using mass spectrometry, peptide fragments from a digested protein can be detected as mass spectral signals, which are matched to the theoretical peptide mass spectrum based on the protein sequence database to identify the protein. Currently, advanced mass spectrometry can identify approximately 12000 proteins in single human cells; the detection sensitivity can even be improved by using SRM/MRM technology [4,5]. However, mass spectrometry has its inherent limitations in protein identification, including the requirement for the large amount of samples, low identification rates for low-abundance proteins and low reproducibility from different laboratories [6,7].…”
mentioning
confidence: 99%